2019
DOI: 10.11604/pamj.2019.32.182.15344
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use and associated factors among sexually active female adolescents in Atwima Kwanwoma District, Ashanti region-Ghana

Abstract: Introduction Unintended pregnancies and adolescent childbearing are on the increase in Sub-Saharan Africa. In Ghana, 14% of adolescents aged 15-19 are already mothers or pregnant with their first child. Most of these pregnancies are associated with poor outcomes such as miscarriages, stillbirths, unsafe abortions and other complications that might result in infant or mortality. In addition, sexually-active adolescents (16-19 years) are at higher risk of contracting STIs. Evidence suggest that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 11 publications
(13 reference statements)
2
32
1
1
Order By: Relevance
“…This finding is supported by other previous studies in Ghana where at least 90% of the participants had heard of contraceptives. 17,18 However, this finding differs from those found in India where only 51% of school going adolescent girls had heard of contraceptives. 19 The reason for this disparity could be attributed to religious and cultural differences contributing to such knowledge awareness gap.…”
Section: Knowledge and Use Of Contraceptivescontrasting
confidence: 60%
See 2 more Smart Citations
“…This finding is supported by other previous studies in Ghana where at least 90% of the participants had heard of contraceptives. 17,18 However, this finding differs from those found in India where only 51% of school going adolescent girls had heard of contraceptives. 19 The reason for this disparity could be attributed to religious and cultural differences contributing to such knowledge awareness gap.…”
Section: Knowledge and Use Of Contraceptivescontrasting
confidence: 60%
“…However, only 45.1% of them knew at least three methods of contraception. Agyemang et al 18 reported similar findings where about 89% of the participants knew at least one method and only 25% and 31% respectively could mention other methods such pills and injectable. Most of the participants (58.1%) got information regarding contraceptives from friends, health facilities (52%), family members (24.7%) and media (23.7%).…”
Section: Knowledge and Use Of Contraceptivesmentioning
confidence: 79%
See 1 more Smart Citation
“…In Ghana, existing published studies on contraceptive use/family planning have disproportionately focused on women [18,19] and female adolescents [20,21] with much less attention to men, leading a dearth of evidence on male contraceptive use.…”
Section: Policy Dubbed a Road Map For Repositioning Family Planning Imentioning
confidence: 99%
“…The use of modern contraceptives and its associated factors among women age (15-49) have been documented in Ghana (Agyemang, Newton, Nkrumah, Tsoka-Gwegweni, & Cumber, 2019;Aviisah et al, 2018;Geelhoed et al, 2002;Grindlay et al, 2018;Kebede, Abaya, Merdassa, & Bekuma, 2019;Nonvignon & Novignon, 2014;Nyarko, 2020). However, utilization of modern contraceptives specifically among women with induced abortion history is underreported despite their vulnerability.…”
Section: Introductionmentioning
confidence: 99%